Photographic assessment of nasal morphology following rapid maxillary expansion in children - da Silva Filho, Omar Gabriel [UNESP]; Lara, Tulio Silva [UNESP]; Ayub, Priscila Vaz; Cardoso Ohashi, Amanda Sayuri; Bertoz, Francisco Antônio [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2011)
Objective: The aim of the present study was to use facial analysis to determine the effects of rapid maxillary expansion (RME) on nasal morphology in children in the stages of primary and mixed dentition, with posterior cross-bite. Material and Methods: Facial photographs (front view and profile) of 60 patients in the pre-expansion period, immediate post-expansion period and one year following rapid maxillary expansion with a Haas appliance were evaluated on 2 occasions by 3 experienced orthodontists independently, with a 2-week interval between evaluations. The examiners were instructed to assess nasal morphology and had no knowledge regarding the content of the study. Intraexanniner and interexanniner agreement (assessed using the Kappa statistic) was acceptable. Results: From the analysis of the mode of the examiners' findings, no alterations in nasal morphology occurred regarding the following aspects: dorsunn of nose, alar base, nasal width of middle third and nasal base. Alterations were only detected in the nasolabial angle in 1.64% of the patients between the pre-expansion and immediate post-expansion photographs. In 4.92% of the patients between the immediate post-expansion period and 1 year following expansion; and in 6.56% of the patients between the pre-expansion period and one year following expansion. Conclusion: RME performed on children in stages of primary and mixed dentition did not have any impact on nasal morphology, as assessed using facial analysis.
Keywords: Palatal expansion technique; Nasal bone; Airway resistance; Morphology